Noninvasive Assessing Low Back Pain by a Novel Near‐Infrared Spectroscopy Flexible Probe With the Aid of Cupping Protocol - Zhang, Bowen; Lin, Yu; Yao, Bo; Li, Ting (Journal of biophotonics, 2024)
ABSTRACT Low back pain (LBP) is the leading cause of disability worldwide, yet its quantitative and noninvasive assessment remains challenging. Considering that near‐infrared spectroscopy (NIRS) became a promising noninvasive tool for monitoring muscle and cupping therapy could regulate muscle blood flow to relieve LBP, we attempted to incorporate cupping and hemodynamics monitoring in muscle tissue by NIRS to assess LBP. We collected 3‐min NIRS recordings on 12 LBP patients and 12 healthy subjects before and after 20‐min cupping. Initially, no significant hemodynamic differences were observed between the groups. After cupping, the concentration changes of oxy‐hemoglobin (Δ[HbO2]) in the emitter‐detector channel parallel to spine unexpectedly exhibited that LBP was remarkably lower by approximately 67% compared with the controls. This study highlighted the potential of combining NIRS and cupping protocol as a quantitative assessment technique for LBP, also providing a new idea for clinical integration of novel optical assessment technologies. We integrated cupping and hemodynamics monitoring via NIRS to evaluate LBP. After cupping, the concentration changes of oxy‐hemoglobin (Δ[HbO2]) in the emitter‐detector channel parallel to spine exhibited that LBP was remarkably lower by approximately 67% compared with the controls, which provided a quantitative assessment technique for LBP.